MicroRNAs in health and disease - K Rama; P.V.L.N Srinivasa Rao; Aparna R Bitla (Journal of Clinical and Scientific Research, 2017)
MicroRNAs (miRNAs) are a class of endogenous small non-coding RNAs about 21-25 nucleotides in length and account for 1%-5% of the genome. Ever since its discovery in 1993, these molecules have attracted researchers due to their crucial role in regulating gene expression. Dysregulation in miRNA expression profile could serve as molecular signatures for identifying diseases. These have found applications in a number of diseases including cancer, wherein they may be useful for as biomarkers in cancer diagnosis as well as serve as therapeutic targets. This review provides an update on the evolution of miRNAs in the field of medicine and its future therapeutic applications.